Comparative study on gonad development in Rainbow Trout (Oncorhynchus mykiss) reared in fresh and brackish water in the Yazd Province - A. Falahti marvast1; B. Majazi amiri2; M. Alizadeh3; B. Abtahi4 (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2005)
Rainbow trout (Oncorhynchus mykiss) weighting 200±5 grams were used in this study to compare their gonad development in fresh and brackish water in Yazd Province. The culture period lasted 140 days from October to March 2003 during which time the temperature (13.8±0.6), pH (8.18±0.12) and dissolved oxygen (6.2±0.1 1) of fresh and brackish water were kept nearly constant. The salinity of fresh and brackish water was 0.4 -0.5 and 14.3-14.7ppt respectively. The fish were fed common commercial trout food (Chineh GFT2) based on temperature and biomass. Histological studies indicated that the gonad development is accelerated in brackish water where the males mature two month earlier than those reared in freshwater. The Gonadosomatic index (GSI) also affirmed the gonad development (P<0.05).